1989
DOI: 10.1039/f19898502953
|View full text |Cite
|
Sign up to set email alerts
|

Shape-selective adsorption of aromatic molecules from water by tetramethylammonium–smectite

Abstract: The adsorption of aromatic compounds by smectite exchanged with tetramethylammonium (TMA) has been studied. Aromatic compounds adsorbed by TMA-smectite are assumed to adopt a tilted orientation in a face-to-face arrangement with the TMA tetrahedra. The sorptive characteristics of TMA-smectite were influenced strongly by the presence of water. The dry TMA-smectite showed little selectivity in the uptake of benzene, toluene and xylene. In the presence of water, TMA-smectite showed a high degree of selectivity ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
118
0
7

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(133 citation statements)
references
References 1 publication
(1 reference statement)
8
118
0
7
Order By: Relevance
“…These results indicate that bromoxynil adsorption by organo-bentonite is dependent on the molecular size and chemical structure of the organic cation pre-adsorbed on bentonite surfaces, as previously suggested in other cases 17) . These results are in agreement with El-Nahhal 18) who emphasized the influence of the partial saturation of bentonite surfaces (ϳ60% of the cation exchange capacity of bentonite) and the size of the organic cation pre-adsorbed by bentonite.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…These results indicate that bromoxynil adsorption by organo-bentonite is dependent on the molecular size and chemical structure of the organic cation pre-adsorbed on bentonite surfaces, as previously suggested in other cases 17) . These results are in agreement with El-Nahhal 18) who emphasized the influence of the partial saturation of bentonite surfaces (ϳ60% of the cation exchange capacity of bentonite) and the size of the organic cation pre-adsorbed by bentonite.…”
Section: Resultssupporting
confidence: 68%
“…It has been shown that the interaction of organic molecules with modified clays, and/or soil organic matter occurred via portioning, according to the octanole/ water-partitioning coefficient 16) . Furthermore, the shape of the isotherm tends to be L-type 17) and adsorption occurs as the Longmuir type at various pH values, due to changes in the electronic form of bromoxynil as a result of pH changes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, used FTIR to show that water preferentially hydrates the organic cations in TMA and TMPA organoclays and not the siloxane surface. Lee et al (1989) found that water sorption by TMA limited the sorption of aromatic molecules larger than benzene by TMA-smectites. Sheng et al (1997) found that the heterogeneous charge density of smectites noted by Stul and Mortier (1974) leads to micropores with a heterogeneous size distribution in TMPA-smectites.…”
Section: Introductionmentioning
confidence: 99%
“…Various organoammonium exchanged montmorillonites have been synthesized, and the properties and applications have been investigated as so-called "organopbilic clays" which swell in organic solvents to form a thixotropic gel (Jordan, 1950;Jones, 1983). These organoammonium-clays have been studied as a chromatographic stationary phase (Bondarenko et al, 1982), shape selective adsorbates (Barrer, 1978), sorbents for organic contaminants dissolved in water (Lee et al, 1989(Lee et al, , 1990Boyd et al, 1988aBoyd et al, , 1988bJaynes et al, 1991), catalysts (Cornelis and Laszlo, 1982), rheology controlling agents in a wide variety of solvent systems (Jones, 1983), and so on. The modifications have provided new ways to utilize swelling clay minerals in practice.…”
Section: Introductionmentioning
confidence: 99%